Nutritive values of fodders at different seasons and altitudes in Gandaki River Basin of Nepal - Shah, Manoj Kumar; Tamang, Bir Bahadur; Dhakal, Bishnu; Chaudhary, Pashupati; Shrestha, Snehi; Chhetri, Netra (Journal of Agriculture and Natural Resources, 2019)
This study aimed to assess the seasonal and ecological variation of chemical and nutritional values of locally preferred fodders in Gandaki River Basin (GRB) areas. The study was conducted in four altitudinal gradients viz.